1979
DOI: 10.1007/bf01409393
|View full text |Cite
|
Sign up to set email alerts
|

Experimental beta-decay energies of several neutron-rich nuclides with mass number 131?A?146

Abstract: With sources obtained from the on-line mass separator LOHENGRIN the beta-decay energies of 13~Sn, 134Sb, 135'~36Te, ~'3'146Ba and 146La have been determined from measured fl-endpoint energies. The experimental values are compared with the predictions of several mass formulae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

1980
1980
1993
1993

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 13 publications
1
4
0
5
Order By: Relevance
“…From the /~-endpoint energies given in Table 1, a consistent Q~-valuc of 6,620+ 70 keV is obtained for the 6.2s isomer of 146La. This value agrees within errors with the Qa-value reported in our earlier study [6]; but there, this value was attributed to the 10 s isomer. The decay energy of this isomer must be considered as uncertain; it is planned to study its decay again in the near future at the LOHENGRIN mass separator.…”
Section: -57~lt89supporting
confidence: 89%
See 2 more Smart Citations
“…From the /~-endpoint energies given in Table 1, a consistent Q~-valuc of 6,620+ 70 keV is obtained for the 6.2s isomer of 146La. This value agrees within errors with the Qa-value reported in our earlier study [6]; but there, this value was attributed to the 10 s isomer. The decay energy of this isomer must be considered as uncertain; it is planned to study its decay again in the near future at the LOHENGRIN mass separator.…”
Section: -57~lt89supporting
confidence: 89%
“…The main aim of the present study was the search for nuclear structure effects in the mass region A~150. Therefore, in addition to the new Q~-measurements described above, some /?-decay energies obtained in earlier studies [5,6,8] have been re-evaluated. In this new evaluation, an improved data handling procedure to decompose the complex /?-spectra and to subtract the background was applied, which had been developed in the meantime [11].…”
Section: ~*'71n 57~d90mentioning
confidence: 98%
See 1 more Smart Citation
“…The sum of the placed y-ray intensities (including intensities of the tentatively placed lines) amounts to 97% of the total y-ray intensity. Using the 7-ray intensities corrected for internal conversion and the Qp-value of 6660 __+ 120 keV [ 11 ], we have calculated the B-feedings and log ft values [20] for all excited levels. In this calculation, the B-feedings to the ground state of 146Ce and to levels with spin values of 2 or less were assumed to be zero.…”
Section: Ce Level Schemementioning
confidence: 99%
“…The isomerism in 146La was first reported by Monnand et al [10] who measured the half-lives of the low-and high-spin isomers to be 6.2 and 10.0 s, respectively. Keyser et al [ 11 ] measured the Q~-values for the two isomers of ~46La at the mass separator LOHENGRIN and reported that the high-spin isomer was the ground state of 146La, although this assignment was not confirmed by the results of later Q~-value measurements [12][13][14]. The decay of the low-spin 2-isomer of 146La with T~/2= 6.27 s has been investigated at the mass separator TRISTAN, where this isomer is predominantly produced through the /?…”
Section: Introductionmentioning
confidence: 98%